What Is the Therapeutic Reference Range for Levetiracetam? Grand Round/A Case Study. Issue 3 (June 2022) - Couderc, Sylvain; Chouchane, Mondher; Saint-Marcoux, Franck
Abstract: The Therapeutic Drug Monitoring guidelines of Arbeitsgemeinschaft für Neuropsychopharmakologie und Pharmakopsychiatrie had proposed a therapeutic reference range of 10–40 mg/L for levetiracetam in 2011. In the first version of the 2017 update, it was changed to 20–40 mg/L; however, 5 months later, in an erratum version, it was changed back to 10–40 mg/L. In this study, the authors agree with the range to 10–40 mg/L but discuss to what extent a wider interval may be proposed for certain patients.